The Climate Change Dynamics and its Impact on the Wheat Productivity in Pakistan: A VAR Approach - Mehmood, Naveed; Khalil, Samina (Asian Journal of Agriculture and Rural Development, 2013)
The protracted change in climatic conditions because of the natural or anthropogenic activities is termed as climate change. It is mainly caused by human induced emission of greenhouse gases like Carbon dioxide CO2, Methane CH4, Nitrous oxide NO2. These gases trap the sunlight, rising the earth’s temperature and altering the pattern of precipitation, humidity across countries and causing some sever damages to the economies. Yearly data (from 1971 to 2009) published by the Metrological Department of Pakistan and Agriculture Statistics of Pakistan is being used. Vector Autoregressive Modeling is applied to study the impact of the climate change on wheat productivity. The result of the model shows that the rising temperature leads to reduction in output as the variation in the wheat productivity has been brought mainly by the variation in the temperature that is 25 percent in the tenth period as shown by the variance decomposition.